Re‐casting experience and risk along rocky coasts: A relational analysis using qualitative GIS. Issue 1 (30th September 2018) - Kamstra, Peter; Cook, Brian; Edensor, Tim; Kennedy, David M.
Abstract : This study invites readers to experience risk on Australia's hazardous rocky coasts with the rock fishing community. In the paper, we offer an understanding of risk that is relational, a process that emerges within human–environment interactions in a dynamic coastal space that is constantly changing. Exploring the in situ and ongoing sensory attunement of the fishers, we contend, expands upon the quantitative understandings that tend to be deployed by risk managers, offering an innovative approach to conceptualising risk. In identifying how fishers perceive and experience a rocky coastal location in Sydney, Australia, we track rock fishers' movements using global positioning systems (GPS), undertake participant observation, and draw on video footage, semi‐structured interviews and participatory sketch maps. In doing so, fishers' perceptions of socio‐environmental stimuli were spatially represented in a GIS, with sketch mapping being the proxy and/or the window into perception–environment relations that produce risk. We contend that the findings show that experienced fishers are more capable of anticipating and reacting to hazardous situations "safely" because they are more attuned to how changing coastal conditions affect risk. This study draws attention to the spatial and temporal phenomena that drive risk perceptions as well as the implications for future perception‐oriented research that adopt a relational understanding. Abstract : This study explores how fishers' perceive and experience a rocky coastal location in Sydney, Australia, by tracking rock fishers' movements using global positioning system (GPS), undertake participant observation, and draw on video footage, semi‐structured interviews, and participatory sketch maps. In doing so, fishers' perceptions of socio‐environmental stimuli were spatially represented in a GIS, with sketch mapping being the proxy/windows into perception–environment relations that produce risk. We contend that the findings show that experienced fishers are more capable of anticipating and reacting to hazardous situations "safely" because they are more attuned to how changing coastal conditions affect risk.